2005
DOI: 10.1007/s10330-004-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Survivin Expression in the Subtypes of Lymphoma

Abstract: Objective: To detect the expression of survivin in subtypes of lymphoma and its value in classifying subtypes of lymphoma. Methods: Paraffin-embedded samples collected from 219 cases of lymphoma and 13 cases of lymph node reactive proliferation from affiliated hospitals of Sun Yat-sen University during 2001-2003 were examined for the expression of survivin by using immunohistochemical staining. Reverse transcription-polymerase chain reaction (RT-PCR) was used to detect the mRNA expression of survivin in K562, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Although the recent study demonstrated KLF12 enhances anoikis resistance of lung metastatic cancer cells via regulating cell cycle progression [61], our findings in this study showed another mechanism of that the loss of KLF12 elevating the expression of survivin and its related intrinsic apoptotic pathway. Overexpression of survivin, which belongs to the inhibitor of apoptosis (IAP) proteins, may lead to cancer cell invasiveness, poor patient prognosis and low survival rates [62, 63]. The survivin anti-apoptotic network is mediated through the survivin-XIAP complex, which subsequently inhibits the activation of caspase-9 and the cleavage of caspase3 and PARP.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recent study demonstrated KLF12 enhances anoikis resistance of lung metastatic cancer cells via regulating cell cycle progression [61], our findings in this study showed another mechanism of that the loss of KLF12 elevating the expression of survivin and its related intrinsic apoptotic pathway. Overexpression of survivin, which belongs to the inhibitor of apoptosis (IAP) proteins, may lead to cancer cell invasiveness, poor patient prognosis and low survival rates [62, 63]. The survivin anti-apoptotic network is mediated through the survivin-XIAP complex, which subsequently inhibits the activation of caspase-9 and the cleavage of caspase3 and PARP.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, survivin expression was observed in most human NHLs of various morphological subtypes and often exceeded 70%-80% of examined cases. In the study of Gu and Lin (2004) the differences of survivin expression between high and low grade lymphomas were found. In the latter group survivin expression was observed in 20%-40% of cases depending of its histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being overexpressed in oral cancers, survivin was found to be over-expressed in patients with colorectal carcinoma and lymphoma (20). Two studies revealed that expression of survivin was significantly higher in adenomatous polyps and adenocarcinoma as compared to normal colorectal mucosa (21,22).…”
Section: The Expression Of Survivin In Human Cancersmentioning
confidence: 99%